Evidence-based patient/public voice: a patient and public involvement audit in the field of sexual health. Issue 4 (18th September 2018) - Meyrick, Jane; Gray, Debra
Abstract : Background: The National Health Institute constitution enshrines the central role of patient and public involvement (PPI) in order to place patients at the heart of the NHS. The sexual health field presents unique challenges for PPI in the tension between current PPI practice versus the need for confidentiality/feelings of shame/stigma. However, there is little evidence around the goals, evaluation measures or theoretical underpinnings of PPI. Objectives: In order to improve current PPI practice in the sexual health field, audits were carried out on PPI plans in both service and research sectors. Methods: 18 local sexual health service contacts completed the audit through snowballing. The tool was refined and five research projects completed the audit from the Health Protection Research Unit in BloodBorne and Sexually Transmitted Infections. Responses were collated and a thematic analysis by two independent researchers carried out. Common areas for improvement were identified. Results: Audit tool responses evidenced wide variability in practice. Issues included conflation of PPI work and qualitative research; limited 'patient satisfaction' approaches; lack of PPI goals; methodological reliance on 'visible' methods such as focus groups; lack of responsiveness around patient needs and poor resourcing of PPI work. Research specific issues included 'late' PPI after key decisions had been made and poor lay summary validity. Discussion: Two audits evidenced a range of areas for improvement of PPI practice in sexual health. Clear definition of 'what PPI is for' aligned with evaluation measures would begin to build an evidence base for the contribution of patient voice.